2019
DOI: 10.1016/j.celrep.2019.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Myosin VII, USH1C, and ANKS4B or USH1G Together Form Condensed Molecular Assembly via Liquid-Liquid Phase Separation

Abstract: Highlights d Microvilli tip-link proteins MYO7B, USH1C, and ANKS4B condensate via phase separation d Hair cell tip-link proteins MYO7A, USH1C, and USH1G also form condensates d Strong multivalent interactions are required for tip-link condensate formation d MYO7A mutations in USH1 patients impair MYO7A/USH1C/ USH1G condensate formation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 64 publications
(126 reference statements)
0
37
0
Order By: Relevance
“…IDPs are known to drive the formation of both organelles by liquid-liquid phase separation (LLPS) (9,70,71). Recently, it has been suggested that SANS generates protein condensates via LLPS as part of the tip-link complex in stereocilia of inner ear hair cells (33). SANS may change the material properties in the tip-link complex and in the absence of SANS, the tip-link complex of hair cells loose its integrity (32).…”
Section: Sans Interacts Through An Intrinsically Disordered Region Wimentioning
confidence: 99%
See 1 more Smart Citation
“…IDPs are known to drive the formation of both organelles by liquid-liquid phase separation (LLPS) (9,70,71). Recently, it has been suggested that SANS generates protein condensates via LLPS as part of the tip-link complex in stereocilia of inner ear hair cells (33). SANS may change the material properties in the tip-link complex and in the absence of SANS, the tip-link complex of hair cells loose its integrity (32).…”
Section: Sans Interacts Through An Intrinsically Disordered Region Wimentioning
confidence: 99%
“…Pathogenic variants in USH1G cause human USH1, a ciliopathy characterized by sensory neuronal degenerations leading to profound hearing loss, vestibular dysfunction and vision loss in the form of Retinitis pigmentosa (RP) (24). While in the inner ear the essential roles of SANS in hair cell differentiation and the mechano-electrical signal transduction complex can well explain the pathophysiology in USH1G (31)(32)(33), the ophthalmic pathogenesis in the retina is still puzzling (78). Links between the USH1G protein SANSor any other USH1 proteinsand the splicing machinery of cells has not been reported yet.…”
Section: Sans/ush1g Mutations Lead To Ush Due To Splicing Defects In mentioning
confidence: 99%
“…The extracellular domains of CDH23 and protocadherin 15 (PCDH15) bind to one another to form the stereociliary tip link required to open stretch-activated channels located at the tip of the shorter stereocilium. For simplicity, only one copy of each protein is shown in these diagrams even though the myosin-7's and the cadherin superfamily proteins are likely to function as homodimers or higher-order oligomers, and the complexes themselves may form protein condensates (11). For a more detailed summary of protein interactions, see Ref.…”
Section: Conflict Of Interest-mentioning
confidence: 99%
“…Whereas most of the binary interactions in the IMAC exhibit affinities in the range of ~1-5 µM (8,12,13), the ANKS4B Cterminus binds to the USH1C N-terminal PDZ domain with a much higher affinity in the nM range (12,13). The extensive network of multivalent interactions among IMAC components may also lead to liquid-liquid phase separation upon complex formation (32).…”
Section: Introductionmentioning
confidence: 99%